Pengaruh akses informasi kesehatan reproduksi remaja dengan perilaku ibu dalam memberikan pendidikan seksualitas - Niken Meilani; Nanik Setiyawati; Munica Rita Hernayanti (Poltekkes Kemenkes Yogyakarta, 2012)
Source of Adolescent Reproductive Health Information and Behavior of Early Adolescent Mother in Providing Sexuality Education; The incidence of premarital sex and HIV positive in adolescents is increasing. Teens need information about sexuality, and the role of mothers in the early adolescent is very important. The purpose of this research is to find out the effect of source of adolescent reproductive health information and mother's behavior in giving the sexuality education. This type of research is an analytic correlational with cross sectional approach. This research due on June-July 2012. Sample of 92 mothers of adolescents aged 10-14 years belonging to the Pilot Project Bina Keluarga Remaja by cluster sampling. Data collection by interview using a questionnaire. Data analysis includes univariate, bivariate and multivariate analyzes. The results showed only 44.6% of mothers who behaved well in giving sexuality education. There are relationship between source of ARH information from health provider (p=0 001), society organizations (p=0.024), electronic media (p=0.022) and from mass media (p=0.003) While from the above variables are most influential is source of ARH information from health provider (p=0.006, OR= 3.78)